Potential environment and socio-economic impact of biofuel production in Malaysia: a preliminary review. Issue 1 (April 2021) - Mohan, D; Essam, Yusuf; Katman, H Y B; Ahmed, A N; Shamsuddin, A H
Abstract: Malaysia is the second-biggest palm oil producer worldwide. Roughly 5.9 million hectares of area is planted with oil palm in Malaysia as recorded in 2019, making the palm oil industry one of the main income-generating industries for the country's economy. As the palm oil industry in Malaysia grows, concern has been raised as several environmental and socio-economic issues are linked with the expansion of oil palm cultivation. The findings of this research contributes towards the preliminary investigation on the effect of biofuel demand in Malaysia on potential deforestation, greenhouse gas emissions due to land use changes and water pollution due to palm oil mill effluent (POME); and the effect of biofuel demand in Malaysia on other types of crops.